Effects of synthetic alkamides on Arabidopsis fatty acid amide hydrolase activity and plant development. (February 2015) - Faure, Lionel; Cavazos, Ronaldo; Khan, Bibi Rafeiza; Petros, Robby A.; Koulen, Peter; Blancaflor, Elison B.; Chapman, Kent D.
Graphical abstract: Synthetic lipids structurally similar to naturally-occurring alkamides shed light on enzymatic properties of an Arabidopsis amidase and the metabolism of alkamides in plants. Highlights: Synthetic "hybrid" alkamide compounds were synthesized. Synthetic alkamides were tested with fatty acid amide hydrolase (FAAH). Two alkamides enhanced FAAH activity toward N -acylethanolamines. Alkamides enhanced FAAH activity by interfering with product inhibition. Abstract: Alkamides and N -acylethanolamines (NAEs) are bioactive, amide-linked lipids that influence plant development. Alkamides are restricted to several families of higher plants and some fungi, whereas NAEs are widespread signaling molecules in both plants and animals. Fatty acid amide hydrolase (FAAH) has been described as a key contributor to NAE hydrolysis; however, no enzyme has been associated with alkamide degradation in plants. Herein reported is synthesis of 12 compounds structurally similar to a naturally occurring alkamide ( N- isobutyl-(2 E, 6 Z, 8 E )decatrienamide or affinin) with different acyl compositions more similar to plant NAEs and various amino alkyl head groups. These "hybrid" synthetic alkamides were tested for activity toward recombinant Arabidopsis FAAH and for their effects on plant development ( i.e., cotyledon expansion and primary root length). A substantial increase in FAAH activity was discovered toward NAEs in vitro in the presence of some of these synthetic alkamides, such as N -ethyllauroylamide (4 ). This "enhancement" effect was found to be due, at least in part, to relief from product inhibition of FAAH by ethanolamine, and not due to an alteration in the oligomerization state of the FAAH enzyme. For several of these alkamides, an inhibition of seedling growth was observed with greater results in FAAH knockouts and less in FAAH over-expressing plants, suggesting that these alkamides could be hydrolyzed by FAAH in planta . The tight regulation of NAE levels in vivo appears to be important for proper seedling establishment, and as such, some of these synthetic alkamides may be useful pharmacological tools to manipulate the effects of NAEs in situ .